Assessing the Value of a Fellowship Program and Community of Practice at the Intersection of Data Science and Library and Information Science. - Goldman, Crystal; Mitchell, Erik T. (Portal: Libraries & the Academy, 2024)
The intersection of Data Science (DS) and Library and Information Science (LIS) is rapidly developing, with a notable need for ongoing transdisciplinary training between practitioners in these two fields. The LIS Education and Data Science Integrated Network Group (LEADING) fellowship program and its ancillary community of practice (CoP) showcase a unique response to this continuing learning need. In order to assess the impact of the fellowship and CoP, this study utilized a sequential mixed methods design, which adapted the value creation framework (VCF) to examine participants' engagement with, and their perceived value of, their LEADING experience. Using the five indicators of the VCF (immediate, potential, applied, realized, transformative) and DEI-centered values, the study results show clear evidence of themes that are reported in the literature as highly influential in CoP value perception (connectedness, emotional engagement, and community values).